The Downside of Displaying Agentic Values: Evidence from Shareholder Activism - DesJardine, Mark R.; Shi, Wei (Organization Science, 2023)
Activist shareholders face a challenging task in preemptively identifying executives who they perceive might destroy shareholder value—before harm is done. We develop a framework where activist shareholders resolve this problem by forming attributions about executives’ intentions based on their displays of agentic values, which reflect independence and control. For activist shareholders, a strong display of independence can evoke concerns that an executive will act without the regulation of shareholder input, and a strong display of control can create concerns an executive will engineer governance provisions to their own benefit. As such, we hypothesize that above-average agentic value displays by CEOs increase the likelihood firms are targeted by shareholder activists. Extending our theory, we argue the positive effect that agentic value displays have on attracting shareholder activism is stronger when CEOs permit higher spending on corporate and stakeholder investment, both of which can exacerbate shareholder harm when executed poorly. We also posit that activism campaigns driven by CEOs’ agentic value displays will largely come from activist shareholders seeking to exert their own control over agentic-speaking CEOs. Using data on shareholder activism campaigns at US-based companies from 2003–2018, we find support for our hypotheses. We discuss multiple theoretical implications for research on corporate governance, stakeholder management, and investor relations.